FABRICATION AND CHARACTERIZATION OF ALOE VERA AND TEA TREE OIL LOADED ANTIMICROBIAL NANOFIBEROUS DRESSING - Memon, Heer; Memon, Anwar Ahmed; Ansari, Abdul Qadir; Otho, Aijaz Ali (LIAQUAT MEDICAL RESEARCH JOURNAL, 2023)
Skin infections due to microbes are reported with high spread and reportedly affected one –third of the world population. Connective tissue cells produce collagen and connective tissue fibers to heal wounds of skin and white blood cells produce antibodies to fight against harmful microbes. This study presents the process of synthesis of nanofiberous dressing loaded with Aloe vera and tea tree oil. Aloe Vera and Tea tree oil contain glucomannan and terpinin-4-ol, which help in the production of collagen and kill microbes. The surface morphology of prepared dressing was studied using Scanning Electron Microscope micrographs. The average diameter of nanofibers was measured to be 137.32nm. Fourier transform infrared spectroscopy of nanofiberous dressing confirmed the loading of aloe vera and tea tree oil. Drug release profile was analyzed by UV-vis spectroscopy. It was observed that 100% drug released within 12 minutes. The antimicrobial properties of prepared fibers against Aspergillus Niger (fungi) and Escherichia coli (bacteria) were systematically evaluated. The results showed that aloe vera- tea tree oil composite fibrous dressing was found to be effective for antimicrobial activity.